ANALISA SUMBER-SUMBER PERTUMBUHAN EKONOMI FILIPINA PERIODE 1994-2003 - VICTOR SIAGIAN (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
Economic crisis hit South East Asia countries after depreciation ofThailand’s currency toward US dollar. The indicator of economic crisis reflectedby decreasing of economic growth. This research describes empirical phenomenonof economic growth in Philippine, using analysis method, dynamic model “ErrorCorrection Model” (ECM).In the short run, significant contributions toward economic growth inPhilippine, caused by foreign investment and domestic debt. In the long run,positive and significant contribution toward economic growth caused by export,import, domestic investment, saving and government expenditure, macroeconomicvariables. Positive but not significant contribution caused by foreign investment.Foreign and domestic debt caused negative and not significant toward economicgrowth. This research can be used as one of references for improving economicgrowth of Indonesia.